Pengaruh Hubungan Work Life Balance dan Pengembangan Karir Terhadap Retensi Karyawan Dimoderasi oleh Kepuasan Kerja: Studi pada Karyawan PT BPR Bkk Jateng Perseroda - Ramadika Kurnia Chandra; Alimuddin Rizal Rivai (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Work Life Balance and Career Development on Employee Retention, as well as the role of Job Satisfaction as a moderating variable among employees of PT BPR BKK Jateng Perseroda. Employee retention is a crucial issue for organizational sustainability. This quantitative research employed questionnaires as data collection instruments from 88 employee respondents of PT BPR BKK Jateng Perseroda. Data were analyzed using multiple linear regression and moderation analysis with SPSS. Validity tests indicated that all instruments were valid, and reliability tests confirmed the instruments were reliable with high Cronbach's Alpha values. Descriptive findings showed that Work Life Balance, Career Development, Job Satisfaction, and Employee Retention were perceived at a very good level by employees. The regression analysis results indicated that simultaneously, Work Life Balance and Career Development significantly influence Employee Retention, explaining 78.8% of the variance. Partially, both Work Life Balance and Career Development were also proven to have a positive and significant influence on Employee Retention. Furthermore, the moderation test results revealed that Job Satisfaction significantly moderates the relationship between Work Life Balance and Employee Retention, where higher Job Satisfaction strengthens the positive influence of Work Life Balance on Employee Retention. However, Job Satisfaction was not found to significantly moderate the relationship between Career Development and Employee Retention. This study concludes that the company's efforts in improving Work Life Balance and Career Development are crucial for Employee Retention, and the role of Job Satisfaction is highly strategic in strengthening the impact of Work Life Balance.